Static and fatigue experimental tests on a full scale fuselage panel and FEM analyses (Fracture and Structural Integrity, 2015)
A fatigue test on a full scale panel with complex loading condition and geometry configuration has been carried out using a triaxial test machine. The demonstrator is made up of two skins which are linked by a transversal butt-joint, parallel to the stringer direction. A fatigue load was applied in the direction normal to the longitudinal joint, while a constant load was applied in the longitudinal joint direction. The test panel was instrumented with strain gages and previously quasi-static tests were conducted to ensure a proper load transferring to the panel. In order to support the tests, geometric nonlinear shell finite element analyses were conducted to predict strain and stress distributions. The demonstrator broke up after about 177000 cycles. Subsequently, a finite element analysis (FEA) was carried out in order to correlate failure events; due to the biaxial nature of the fatigue loads, Sines criterion was used. The analysis was performed taking into account the different materials by which the panel is composed. The numerical results show a good correlation with experimental data, successfully predicting failure locations on the panel.
Keywords: Multiaxial fatigue; Full scale panel; FE model; Life prediction